PENANAMAN KELAPA GENJAH SEBAGAI ALTERNATIF TANAMAN LAHAN KERING, UNTUK MENDUKUNG PROGRAM PERTANIAN MAJU DAN BERKELANJUTAN - Hady, Lalu Jazuly Khaerul; Afriani, Yunisa; Supiani, Supiani; Putri, Ni Wayan Krisnitha; Prihatiningsih, Dena; Rizqia, Dinda Ayu; Maulana, Randa; Kamuri, Mathildes Inna; Saefatullah, Arsy; Misbahuddin, Misbahuddin (Jurnal Wicara, 2023)
Sukaraja village is a village with fairly low rainfall. This causes various problems in agriculture. The problems generally faced are the difficulty of irrigating agricultural land, and the lack of diversity in the types of plants that can be cultivated due to the lack of knowledge of the villagers about the types of plants that can be cultivated on dry land. This activity aims to find alternative crops in the form of dwarft coconut varieties that quickly adapt to dry land conditions. This activity was carried out with the stages of selecting dwarft coconut seeds, preparing the planting land, planting dwarft coconut seeds, and watering and fertilizing dwarft coconut plants. The results obtained from this activity are the selection of several varieties of dwarft coconut seeds, the utilization of land for planting dwarft coconut seeds ready and in accordance with the implementation method, after the availability of seeds and land then planting dwarft coconut seeds, then maintenance is carried out by watering and fertilizing regularly. Based on the results of research conducted by the author during the Real Work Lecture activities in Sukaraja Village, dwarft coconut plants can be an alternative crop suitable for planting on dry land.